2017
DOI: 10.1016/j.ijbiomac.2017.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial biofilms by carboxymethyl chitosan combined with silver, zinc and copper salts

Abstract: Investigation of the antimicrobial action of carboxymethyl chitosan (CMCh) is among the alternative approaches in the control of pathogenic microorganisms. This study aimed to screen the toxicity using the brine shrimp lethality assay and to investigate the inhibitory activity of carboxymethyl in isolation or in combination with silver nitrate, copper sulfate and zinc sulfate on biofilm formation by Staphylococcus aureus ATCC 6538, Staphylococcus epidermidis ATCC 12228, Kocuria rhizophila ATCC 9341, Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…We want to point out that the adjuvant agent, zinc phthalocyanine, has absorption at the far red region (Kobayashi et al, 2003), and thus does not interfere with the photodynamic effect of the DIBPD. The minimum inhibitory concentration (MIC) of zinc salt or its metal against bacteria was very high (500 µg/ml, or 3.12 mM) (Goncalves et al, 2017;Gugala et al, 2019), much higher than the concentration of adjuvant that we used here. Thus, it is unlikely that the antimicrobial efficacy of PSC observed here was due to the zinc salt in the adjuvant.…”
Section: Optimization Of a Photosensitizer Complex (Psc) Stable Undermentioning
confidence: 65%
“…We want to point out that the adjuvant agent, zinc phthalocyanine, has absorption at the far red region (Kobayashi et al, 2003), and thus does not interfere with the photodynamic effect of the DIBPD. The minimum inhibitory concentration (MIC) of zinc salt or its metal against bacteria was very high (500 µg/ml, or 3.12 mM) (Goncalves et al, 2017;Gugala et al, 2019), much higher than the concentration of adjuvant that we used here. Thus, it is unlikely that the antimicrobial efficacy of PSC observed here was due to the zinc salt in the adjuvant.…”
Section: Optimization Of a Photosensitizer Complex (Psc) Stable Undermentioning
confidence: 65%
“…The weak acid characteristic of (NH4)2SO4 and NaH2PO4 and the weak base characteristic of Na2CO3 and NaHCO3 may be responsible for the larvicidal activities of these inorganic salts; because no mortality of Anopheles stephensi and Culex quinquefasciatus larvae was observed with the neutral inorganic salts sodium chloride (NaCl) and sodium phosphate (Na3PO4) aqueous solutions, even at doses 10 times higher than those tested for the weak acid and weak base inorganic salts (data no shown). Previous studies found that inorganic salts have very interesting antimicrobial [28,29], fungicide (especially Na2CO3 and NaHCO3) [30,31] and insecticide properties [32]. Darriet et al [33] also found that mineral and organic compounds have an impact on the development of larvae because the NPK fertilizer placed in water killed all the Aedes Aegypti larvae before pupation.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles (NPs) can be used for both inhibition of biofilm formation and eradication of already formed ones [108].…”
Section: Nanotechnology-based Antimicrobials Used To Control Biofilmsmentioning
confidence: 99%